Analysis of Employee Work Stress Using CRISP-DM to Reduce Work Stress on Reasons for Employee Resignation - Emral Hakim; Ahmad Muklason (Data Science: Journal of Computing and Applied Informatics, 2024)
Internal audit activities at EPC companies have found a trend of increasing work stress as a reason for employee resignation in the period Q4 2021 - Q1 2023. In implementing ISO 45001:2015 this must be controlled because it is a psychological occupational disease. For this reason, a work stress survey was carried out, the results of which were reviewed using Cross Industry Standard Process for Data Mining (CRISP-DM). Descriptive analysis found a maximum ratio of moderate stress of 66%, light stress of 39%, and severe stress of 9% with a risk matrix in Medium (yellow area). Descriptive analysis found a maximum ratio of moderate stress of 66%, light stress of 39%, and severe stress of 9% with a risk matrix in Medium (yellow area). Diagnostic analysis found a total of 19 questionnaires that affected severe stress and moderate stress. Cluster K-Modes shows 3 clusters being centroids with principal component values explaining around 4.92% of the original feature variance. The deployment of work stress control is carried out through focus group discussion to formulate Socialization, Externalization, Combination, Internalization (SECI) as a follow-up program for organization.